Medical Staff Attitude toward Parents' Participation in the Care of their Hospitalized Children - F Valizadeh; SF Ghasemi (Tehran University of Medical Sciences, 2008)
Background & Aim: Family-centered care, which has become the cornerstone for pediatric nursing practice, supports the integrity of child and family health. It brings families a unique care and improves child and family health. Families are recognized as an essential part of a specialized child care during illness. They are expected to be skilful in child care both in and out of health care facilities. This study was carried out to determine health caregivers' attitude toward parent participation in the care of their hospitalized children at Madani pediatric hospital- Khoramabad in 2004. Methods & Materials: This is a descriptive-analytical study. One hundred and sixty nine caregivers were selected through convenient sampling method. Data were gathered using a questionnaire including demographic and parents' attitude questions. The questionnaire had 36-item. The data were analyzed via SPSS computer software and using descriptive and analytical methods. Results: Results indicated that the average of participants' attitude score was 92.28±12.55. Most of subjects had neutral attitudes toward parents' participation in their children's care. Positive attitude were significantly related with marital status (P<0.04), having children (P<0.04) and being a nursing student (in comparison with medical students) (P=0.04). Conclusion: The caregivers' attitudes toward parents' participation in the care of their hospitalized children were neutral. The students' and staffs' attitudes should be modified by taking part in continuous training programs.